Improving the Graphic Education System through Modern Graphic Programs (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the article, the role of graphic programs in the engineering sciences in the educational system, especially in technical higher education institutions, through them, we can see that the issues related to Build Art technologies, which are the demand of today, can be easily and conveniently solved. The ability to analyze the spatial properties and tasks of subjects is an important component of the graphic preparation of students. In the field of graphic education, development of students' spatial imagination, imaginative analysis of spatial images, activation of mental and cognitive activities of students, development of spatial thinking and imagination, imaginative observation and acceptance of spatial phenomena, shapes, and acquisition of all graphic knowledge and skills, keeping in memory creative qualities such as staying have been adding a significant share to the creation of content.